Ergonomics, Health and Safety - Dirx, J. (Studia Psychologica, 1991)
The following chapters represent a cross-section of current thinking and action in the related fields of Ergonomics, Health and Safety. Inevitably, there is extensive overlap between these three topics. Ergonomics by definition is concerned with the world of work in its broadest sense, that is purposeful activity, there is often an associated monetary gain but this is not an essential aspect; domestic activity and road transport are amongst the obvious exceptions. Health in this context means largely occupational health. Safety is occupational safety with a related excursion into road safety. All this is very much in line with the career of Professor Paul Verhaegen, the inspirer of this volume. Originally trained in medicine, his interests were and are in health, safety and working efficiency within occupational settings, including the effects of cultural differences, a more specialized interest engendered by his long residence in what used to be the Belgian Congo.